PROTOTYPE SISTEM PENGATURAN KECEPATAN KIPAS DC OTOMATIS MENGGUNAKAN SENSOR PIR, SENSOR ULTRASONIK, SENSOR DHT11 BERBASIS MIKROKONTROLER ARDUINO UNO DAN NODEMCU - Rizki Dwi Saputra (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2022)
fan is always ordinary thing at home, human needs fan for comfortable while rest, and lower the temperature of the body if the weather is too hot. But fan brings adverse effect like, the experience pain in certain parts of the body, for example,stiffness due to being exposed to a wind blow of the fan that is always strong against the body.The purpose of making this prototype is to automatically adjust the fan speed based on the distance from the fan to the human. by using an ultrasonic sensor, by using Passive Infrared sensor, we can automatically turn off without pressing any button so that the fan can turn on, and there is also a DHT11 sensor which can make us know the room temperature and humidity of the room being occupied, the fan will automatically turn off if it does not detect humans within 1 minute 40 seconds, in this project we can also turn on or turn off the fan if you really want to turn it on even though no one is in front using the Blynk application, and the temperature and room will also appear on the Blynk application, the microcontroller used is ArduinoUno, and NodeMCU as intermediary for the internet